Analisis Aspek Dominan Dari Dukungan Keluarga Terhadap Sikap Menstruasi Pada Remaja Putri - Ira Rahmawati; Iis Rahmawati; Yessi Eka Safitri (Journal of Health Science and Prevention, 2023)
Adolescents are defined as individuals with an age range of 10-19 years. In Indonesia, 63.9% of girl adolescents had bad behavior in menstrual hygiene. This study will analyze the relationship between family support and menstrual hygiene attitudes of adolescent girls and the dominant aspect of family support in Jember and Bondowoso. This study uses an observational design using a cross-sectional approach and data were analyzed using multiple linear regression. The sampling technique used was proportional stratified random sampling with a total sample of 300 female adolescent respondents in rural areas of Jember and Bondowoso. Data retrieval was done by questionnaire via google form link. The results showed that there was a statistically significant relationship between family support and attitudes about menstrual hygiene (p-value = 0.012). The most dominant indicator of family support is the instrumental aspect by providing material or physical support that can support adolescent menstrual hygiene.